The E3 ubiquitin ligase NEDD4 enhances killing of membrane-perturbing intracellular bacteria by promoting autophagy. Issue 12 (2nd December 2017) - Pei, Gang; Buijze, Hellen; Liu, Haipeng; Moura-Alves, Pedro; Goosmann, Christian; Brinkmann, Volker; Kawabe, Hiroshi; Dorhoi, Anca; Kaufmann, Stefan H. E.
ABSTRACT: The E3 ubiquitin ligase NEDD4 has been intensively studied in processes involved in viral infections, such as virus budding. However, little is known about its functions in bacterial infections. Our investigations into the role of NEDD4 in intracellular bacterial infections demonstrate that Mycobacterium tuberculosis and Listeria monocytogenes, but not Mycobacterium bovis BCG, replicate more efficiently in NEDD4 knockdown macrophages. In parallel, NEDD4 knockdown or knockout impaired basal macroautophagy/autophagy, as well as infection-induced autophagy. Conversely, NEDD4 expression promoted autophagy in an E3 catalytic activity-dependent manner, thereby restricting intracellular Listeri a replication. Mechanistic studies uncovered that endogenous NEDD4 interacted with BECN1/Beclin 1 and this interaction increased during Listeria infection. Deficiency of NEDD4 resulted in elevated K48-linkage ubiquitination of endogenous BECN1. Further, NEDD4 mediated K6- and K27- linkage ubiquitination of BECN1, leading to elevated stability of BECN1 and increased autophagy. Thus, NEDD4 participates in killing of intracellular bacterial pathogens via autophagy by sustaining the stability of BECN1.